Health technologies ‘In the wild’: experiences of engagement with computerised CBT - Rennick-Egglestone, Stefan; Knowles, Sarah; Toms, Gill; Bee, Penny; Lovell, Karina; Bower, Peter (Association for Computing Machinery, 2016)
The widespread deployment of technology by professional health services will provide a substantial opportunity for studies that consider usage in naturalistic settings. Our study has documented experiences of engaging with technologies intended to support recovery from common mental health problems, often used as a part of a multi-year recovery process. In analyzing this material, we identify issues of broad interest to effective health technology design, and reflect on the challenge of studying engagement with health technologies over lengthy time periods. We also consider the importance of designing technologies that are sensitive to the needs of users experiencing chronic health problems, and discuss how the term sensitivity might be defined in a technology design context.